Self-powered and high sensitivity ionic skins by using versatile organogel. (August 2022) - Li, Wei; Zhang, Jin; Niu, Jiarong; Jin, Xin; Qian, Xiaoming; Xiao, Changfa; Wang, Wenyu
Abstract: Based on organogels, the new ionic skins with self-powered function are highly desirable to develop sensors, human-machine interaction and flexible wearable devices but remain an enormous challenge to develop. Here, we report an ionic skin device based on organogel with surface microstructure, which is flexible, highly sensitive and conductive. It can convert mechanical energy into electrical energy in the case of compression and release. The ionic skin device can not only be made into a flexible pressure sensor with high sensitivity (6.64 kPa −1 ), but also be assembled into a tensile sensor with high sensitivity (43.02 MPa −1 ) and high linearity (99.41%) in a wide detection range (0–1.1 MPa). what's more, the device generated stable electrical signal outputs (current ~ 1.7 mA, voltage ~ 60 mV), which can be used as ionic skin with self-powered function, which has never been reported on other sensors so far. On the basis of eliminating the external energy storage devices, it is safer and easier to carry. In addition, the organogel can be used as flexible electrodes in capacitive sensor, and good adhesion properties can help to improve the performance of sensors. The organogel has also the function of 3D printing, and can design different structures according to requirements. It shows good performance response in monitoring human physiological signals and motion signals, which provides a new direction for the development of intelligent devices. Graphical Abstract: ga1 Highlights: A novel organogel has flexibility, stretching, conductivity, frost resistance, adhesion, and recyclable properties. Organogel based ionic skin has good sensing properties and self-powered function of direct-current outputs. Ionic skin can convert human kinetic energy into electric energy. Ionic skin can monitor the physiological and motion signals of the human body.